Análisis tafonómico de Littoridina Souleyet, 1852 (Gastropoda: Hydrobiidae) en perfiles holocenos del río Quequén Grande (provincia de Buenos Aires): significado paleobiológico y paleoambiental (Ameghiniana, 2014)
Taphonomic aspects of dense deposits of Liitoridina austraiis (Orbigny) and Litioriáina parchappii (d'Orbigny), from a Holocene outcrop located at the Quequén Grande river, were used as paleobiological and paleoenvironmental indicators to reconstruct the evolution of the estuarine environment between circa 7,000 and 5,000 "e yr BP. Levels with dominance of Liuondina parchappi! correspond to autochtonous fossil assemblages deposited under low energy estuarine conditions. On the other hand. most specimens of Littoridina australis were redeposited and represent transported assemblages. The differences shown by both species are probably related to the energy conditions of the environments where they lived. As Littoridina parchappii is part of a fossil population, it can be considered a good paleobiological and paleoenvironmental indicator whereas Littoridina australis, which basica11y belongs to a taphocoenosis, can be a useful tool to evaluate both paleoenvironmental and depositional conditions such as the relative energy and direction of the dominant currents.